Thrombotic Obstruction of a Melody Valve-in-Valve Used for Prosthetic Tricuspid Stenosis. (October 2015) - Reddy, Yogesh N. V.; Connolly, Heidi M.; Ammash, Naser M.
The percutaneous Melody valve is occasionally used for the treatment of bioprosthetic valve dysfunction and is an attractive option for patients at high risk for repeat operation. Anticoagulation is not routinely recommended following Melody valve placement. We present the case of a young woman who developed subacute spontaneous thrombosis of her Melody valve 15 months after placement. Her clinical status was compromised by severe tricuspid prosthesis stenosis and right-to-left shunting across a small residual atrial septal defect. Surgical replacement was required. To our knowledge, this is the first reported case of spontaneous thrombosis of a Melody valve in the tricuspid position.